The use of advanced analytical techniques for studying the biodegradation of aromatic hydrocarbons - Fisher, Steven J. (Curtin University, 2002)
Two case studies are described where partially biodegraded petroleum residues were collected from the marine environment and analysed to investigate the changes in aromatic hydrocarbons with increasing biodegradation.The first of these studies, involved following the weathering of sea-floor residues from drilling discharges from an offshore petroleum exploration and production platform situated off the coast of North Western Australia. During operations, formation cuttings with adhering oil-based drilling muds were discharged into the ocean via a chute into approximately 125n1 of water, forming a substantial mound at the base of the platform. A suite of seabed sediments was collected from 16 sampling sites at various distances from the platform immediately following the cessation of drilling operations. The distribution of hydrocarbons in the sediment directly under tile cuttings chute was consistent with that found in drilling fluids formulated from a kerosene-like fluid. The samples from more remote sites exhibited the successive enhancement of an unresolved complex mixture relative to the n-alkanes, associated with tile presence of residues from petroleum biodegradation processes. In a subsequent sampling some three years later, a 10 cm core was retrieved from the cuttings pile and divided into 1 cm depth intervals. Samples within 6 cm of the surface of the cuttings pile contained biodegraded residues of the drilling mud, where the extent of biodegradation increased with decreasing proximity to the surface, most likely indicative of aerobic biodegradation. Biodegradation was less evident in the underlying sediments, where anaerobic conditions prevailed.Analysis of the aromatic hydrocarbons in both sets of sediment extracts by using gas chromatography-mass spectrometry (GC-MS) revealed the successive depletion of alkylnaphthalenes, and due to the subtlety of changes in the extent of biodegradation, provided an excellent opportunity to examine the susceptibility of biodegradation towards the individual alkylnaphthalenes in the marine environment. Conventional GC-MS analysis of these mixtures is performed under chromatographic conditions where complete resolution of the mixture is not achieved and several isomers co-elute. The mass spectra of these co-eluting isomers may be so similar that one is unable to differentiate between them, and their abundance may therefore not be determined. Since each isomer has a unique infrared spectrum, however, the abundance of each individual isomer was determined by comparing the infrared spectrum of the co-eluting compounds with the spectrum of each of the isomers. To this end, techniques were developed for the application of direct-deposition gas chromatography - Fourier transform infrared spectroscopy (GCFTIR) to the analysis of the complex mixture of alkylnaphthalenes present in the petroleum. This technique was also extended to discriminate between individual alkylphenanthrene isomers, and to clarify the sorption behaviour of the dimethylphenanthrenes by mordenite molecular sieves. The identification of other compounds of geochemical significance in petroleum is also described.Analyses of' the aromatic hydrocarbons in the contaminated sea-floor sediments using GC-FTIR enabled the unambiguous identification and quantification of each of the dimethylnaphthalene, trimethylnaphthalene and tetramethylnaphthalene isomers present in the samples, from which the relative extents of depletion of each with increasing extent of biodegradation were determined. It was apparent from the considerable differences in the observed susceptibility to biodegradation that a strong relationship exists between the compound structure and its susceptibility to biodegradation, with 1,6-disubstituted polymethylnaphthalenes being preferentially depleted relative to other isomers that lack this feature. The second case study involved tracking the fate (weathering) of hydrocarbons from an accidental release of condensate from a buried pipeline into intertidal coastal (mangrove) sediments in North Western Australia. Sediment samples were collected on nine occasions over a three-year period. Chemical analysis of the saturated and aromatic hydrocarbon components of the petroleum extracts revealed that both hydrocarbon fractions exhibited an increasingly biodegraded profile with increased residence time in the sediments. In a similar manner to the first case study, detailed analysis of the aromatic hydrocarbons using GC-FTIR techniques was performed to determine the depletion of individual alkylnaphthalene isomers with increasing extent of biodegradation. It was apparent that a relationship similar to that observed for the sea-floor sediments exists between the alkylnaphthalene structure and its susceptibility to biodegradation.Changes in the distribution of methylphenanthrene and dimethylphenanthrene isomer mixtures were also studied and the susceptibility to biodegradation amongst these determined in a similar manner. These relative susceptibilities to biodegradation of the aromatic hydrocarbons were then related to the established hierarchy of susceptibilities of the saturated hydrocarbons, in effect providing a second parallel system for the assessment of the extent of biodegradation. Finally, a system of ratios calculated from the relative abundances of selected aromatic hydrocarbons was developed and used as indicators to differentiate between several crude oils that have been biodegraded to varying extents. These parameters also offer promise as indicators of multiple accumulation events in oil reservoirs where petroleum fluids biodegraded to differing extents are mixed.